Implementation of Tiwana Method in a Knowldedge Management System Prototype - Anisah, Siti (Journal of Information Systems and Technology Research, 2023)
Improving customer service really needs to be done by a company. one form of service improvement is to provide convenience to customers to submit financing applications that can be done anytime and anywhere. Knowledge management systems (KMSs) are tools aimed at supporting knowledge management. Utilization of Knowledge Management System (KMS) has a positive impact on the continuity of the organization's business, this happens because KMS is an effective way to translate work experience on an ongoing basis in the form of knowledge. The tiwana framework was chosen for the reason that tiwana has advantages compared to other methods for designing KM. The problem faced by cooperatives is that in submitting financing activities it is still manual, namely customers have to come to the Al Salaam sharia cooperative, this is very inconvenient for customers who want to apply for financing and the absence of a container that accommodates all information related to financing products, the type of marketing media used by Al-Saalam is brochures. The purpose of this research is to develop a knowledge management system to improve customer service with the main focus being to provide loan application features. The method used in this study is the Tiwana framework. The results of the research is a prototype of knowledge management system that can be accessed anytime and anywhere by customers.